Isolation and identification of salmonella sp. from processed minced meat product using polymerase chain reaction method / Che Khuizzatieliana Che Om - Che Om, Che Khuizzatieliana (2017)
Salmonella species has caused foodborne illness all around the world and poultry meat has been identified as one of the sources of Salmonellosis. The main purpose of this study was to isolate and identify Salmonella species from processed minced meat product by using Polymerase Chain Reaction method. A total of three samples of processed minced meat products and two strain Salmonella species were used in this study. The processed minced meat was soaked in the pre enrichment broth and was streaked on Salmonella shigella agar after 24 hours including the pure culture strain. All the samples and the Salmonella sp. strain showed a Gram negative results. The genomic DNA of these samples were then extracted by using boiling lysis method and were proceed to Polymerase Chain Reaction amplification for the detection of Salmonella species by using specific primers. Gel electrophoresis was carried out for the identification of the Salmonella species Out of three sample, only one of the sample showed a positive result on the gel electrophoresis. Detection of the Salmonella species on processed minced meat products indicates the need for greater awareness towards the risk associated with the production and handling of the minced meat.